1995
DOI: 10.1111/j.1467-954x.1995.tb02478.x
|View full text |Cite
|
Sign up to set email alerts
|

Circuits of Schooling: A Sociological Exploration of Parental Choice of School in Social Class Contexts

Abstract: Parental choice of school is one of the main platforms of government education policy and is the centre piece of the Parents Charter. But sociological understanding of choice and choice‐making is woefully underdeveloped. This paper draws on an ESRC study of market forces in education to explore social class variations in choice of school in one specific locality. The complexity of choice‐making is portrayed using data from interviews with parents and it is argued that middle‐class parents are taking full advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
225
1
24

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(257 citation statements)
references
References 10 publications
7
225
1
24
Order By: Relevance
“…Although the means of organizing education has undergone dramatic change in the forty years or more that separated these two studies, what has not changed significantly is the way that these two class groups have experienced the education system. The middle classes have actively strategised a future for their children envisioning them in yet to be achieved positions, whereas the working classes have, for the most part, accommodated within existing social and geographical boundaries (Ball, Bowe et al 1995) 1 . This widely accepted binary division reflects the power of social class in contemporary society in which the middle class regard the educational system as one to be negotiated and if necessary challenged whereas the working class accept its abuse of opportunity with varying degrees of cynicism and resentment and as an introduction to a life to come (Willis 1977).…”
Section: : Estimating Peer Group Effects In Different School Environmmentioning
confidence: 99%
“…Although the means of organizing education has undergone dramatic change in the forty years or more that separated these two studies, what has not changed significantly is the way that these two class groups have experienced the education system. The middle classes have actively strategised a future for their children envisioning them in yet to be achieved positions, whereas the working classes have, for the most part, accommodated within existing social and geographical boundaries (Ball, Bowe et al 1995) 1 . This widely accepted binary division reflects the power of social class in contemporary society in which the middle class regard the educational system as one to be negotiated and if necessary challenged whereas the working class accept its abuse of opportunity with varying degrees of cynicism and resentment and as an introduction to a life to come (Willis 1977).…”
Section: : Estimating Peer Group Effects In Different School Environmmentioning
confidence: 99%
“…For instance, global policies such as school choice typically do for they will have very different spatial implications for families; not all families will have the financial resources, time, or conditions of work, to move children across the city so as to access a school that might be the best choice (Ball et al, 1995). Other families will face not having a choice as their village or town only has one school.…”
Section: Spatial Fetishismmentioning
confidence: 99%
“…Even amongst those who are inclined to 'choose', social factors tend to restrict the choices available in significant ways. In their work in Greater London, Ball et al (1997) identified three main circuits of school (local community comprehensive schools; cosmopolitan elite maintained schools; and local independent schools) and argued that different class fractions tend to choose within one circuit only.…”
Section: Active Consumersmentioning
confidence: 99%